Implementation of Habituation Methods in Instilling Islamic Spiritual Intelligence in Children with Mild Intellectual Disabilities: A Case Study at SLB Putra Idhata Madiun - Syarifah, Syarifah; Cahyanto, Bagus; Paisun, Paisun; Wafa, Ali; Sholihah, Ana Walidatush (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
Although religious education for children with special needs has attracted increasing attention, there remains a limited number of studies examining specific strategies for instilling religious values in students with intellectual disabilities, despite their critical role in character development and spiritual independence. This study aims to analyze the implementation of habituation methods in fostering Islamic spiritual intelligence and to identify the supporting and inhibiting factors at SLB Putra Idhata Madiun. A qualitative approach with a field study design was employed, involving research subjects at SLB Putra Idhata Madiun from May to December 2024. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed using interactive analysis techniques comprising data collection, data reduction, data display, and conclusion drawing. The findings show that the habituation method is implemented consistently through the integration of daily routines such as praying before and after lessons, practicing ablution, performing congregational Dhuhr prayers, cultivating the tradition of greetings, and commemorating Islamic holidays. These results are aligned with the research objectives and reinforce behaviorist theory, which posits that the repetition of routine behaviors can effectively shape cognitive patterns in students with special needs. The study concludes that the spiritual intelligence of children with intellectual disabilities can be effectively developed through structured routines, although its success is highly contingent on the synergy between teacher guidance, parental support, and the broader school environment. Theoretically, this research enriches the literature on inclusive Islamic education, while practically it provides recommendations for schools to enhance creative innovations in religious habituation programs and for parents to strengthen continuous spiritual guidance at home, as well as opening opportunities for further research on adaptive technology-based learning media to support the spirituality of children with intellectual disabilities in more interactive ways.